O Polsce i o Polakach w pozaantologijnych pismach osobistych cudzoziemców XVIII i XIX wieku - Lubas-Bartoszyńska, Regina (Wydawnictwo Naukowe UAM w Poznaniu, 2012)
This text presents some autobiographical writings of foreigners, which concern Poland of 18th and 19th century with the exception of those treated in J. Gintel’s anthology. This is no problem of systematic information concerning Poland’s reality in these centuries which are to be found in commentaries and treaties. We are discussing foreign diaries, memoires and autobiographies of the following authors: G.G. Casanova, Ch.J. de Ligne, J. Michelet, V. Hugo, R. de Chateaubriand, G. Sand, E. and J. de Goncourts. These autobiographical enunciations are treated here as the credible source of information. These personal texts are destined for Polish readers, who feel specific pleasure finding some mentions concerning Poland. The readers encounter Poles as historical persons, artists, writers in the background of historical events, in travel, social and everyday life.
On Poland and Poles in personal writings of the 18th and 19th century foreigners in literary works other than anthologies